Legal and professional accounting regulations as strategic components of financial reporting quality - Anđelković, Danijela; Petrović, Vesna; Liberakos, Ana (Ekonomija - teorija i praksa, 2023)
The basic aim of the research in this paper is to answer the question of whether the financial statements defined by the legislation in the Republic of Serbia, based on the IASB IAS/IFRS project implementation, could be comparable with the EU financial statements in terms of quality. The main reason for this research is to point out the necessity of including other international accounting regulations, such as EU Directive 34, for financial reporting harmonization and standardization needs. The research results show that the existing legal accounting regulations implementation defined by the IFRS has become the limiting factor for financial reporting quality. Additionally, the research results indicate the need to overcome the existing concept of technically oriented accounting and consider a broader, more completely expressed power of financial reporting that includes other non-financial determinants. In order to reach the set aim, the methodology used in this paper includes qualitative research based on secondary data sources. On that basis, the first part of the paper provides an indicator analysis that illustrates the existing financial reporting quality situation as a result of legal and professional accounting regulations implementation in the Republic of Serbia. In the second part of the paper, based on the research results, we provide suggestions for improving accounting regulations for financial reporting quality needs.